PENDAMPINGAN PEMBUATAN TAMAN TEMATIK BERBASIS SUMBER PAKAN DI EKOWISATA LEBAH MADU “ROYAL HONEY” BANJAR SAKAH KECAMATAN SUKAWATI KABUPATEN GIANYAR - I Wayan Suanda; I Gusti Ayu Rai; Kadek Yuniari Suryatini; Dewa Made Alit; Kadek Intan Rusmayanthi (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
Trigona sp. honey bee cultivation as a honey producer has grown quite rapidly after the 2019 COVID-19 pandemic. The Royal Honey Sakah honey bee ecotourism in Gianyar, established in 2017, has also grown rapidly with visitors from both foreign and local tourists. Providing plants as a source of bee food is a priority in Trigona sp. honey bee cultivation. Flowering plants as a source of honey bee food in this ecotourism area are still not comparable to houses (logs containing Trigona sp. honey bee colonies), especially during the prolonged rainy season which causes some plants to produce relatively few flowers. This condition requires the provision of flower plants based on food sources. in the honey bee ecotourism